Mechanisms of myocardial injury and clinical outcomes in patients hospitalised with suspected COVID-19. (14th October 2021) - Bularga, A; Wereski, R; Taggart, C; Lowry, M; Singh, T; Lee, K K; Anand, A; Shah, A S V; Ross, D A; Perry, M R; Dweck, M R; Newby, D E; et al.
Abstract: Background: Myocardial injury is associated with adverse outcomes in patients with COVID-19. However, the prognostic role of myocardial injury in COVID-19 compared to other acute illnesses and the underlying mechanisms of injury are poorly understood. Methods: In a prospective, multi-centre, cohort study conducted in secondary and tertiary care hospitals in Scotland, all consecutive patients with suspected COVID-19 underwent cardiac troponin (ARCHITECTSTAT high-sensitive troponin I (hs-cTnI) assay; Abbott Laboratories) testing in plasma that was surplus to clinical requirements. The results were not reported unless required by the attending clinician. We evaluated the prevalence of myocardial injury, mechanisms and outcomes in all patients. In those with any hs-cTnI concentration above the sex-specific 99th centile the diagnosis was adjudicated according to the 4th Universal Definition of Myocardial Infarction. The primary outcome of all-cause mortality was compared in those with and without myocardial injury and COVID-19 by cox regression adjusted for age, sex, renal function and co-morbidities. Results: A total of 2, 916 (median age 69 [interquartile range, IQR 54–79] years, 53% women) consecutive patients with suspected COVID-19 were followed up for 228 [IQR 203–249] days. Myocardial injury occurred in 26% (750/2, 916) with a median troponin concentration of 66 [35–178] ng/L; the prevalence was 41% (46/112) and 25% (704/2, 804) in those with and without COVID-19, respectively. The most common mechanism was acute non-ischaemic myocardial injury occurring in 80% (37/46) and 71% (502/704) of patients with and without COVID-19, respectively. Type 1 myocardial infarction (2% and 4%), type 2 myocardial infarction (7% and 14%) and chronic myocardial injury (11% and 11%) were less common and only one patient had confirmed myocarditis. In patients with myocardial injury mortality was increased compared to those without (P<0.001 log rank), whether they had COVID-19 (54% [25/46] versus 26% [17/66]) or not (35% [248/704] versus 14% [294/2100]). Myocardial injury was an independent predictor of death in all patients (adjusted hazard ratio [aHR] 2.04, 95% confidence interval [CI] 1.71 to 2.43), but this excess risk was not higher in patients with COVID-19 (aHR 1.58, 95% CI 0.75 to 3.15) compared to those without the condition (aHR 2.01, 95% CI 1.81 to 2.49). Conclusion: Myocardial injury is common in hospitalised patients with suspected COVID-19 whether or not COVID-19 was the cause of their presentation. The majority of patients had acute non-ischaemic myocardial injury rather than a defined cardiac condition. Despite this the presence of myocardial injury was an independent predictor of death in all hospitalised patients. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): British Heart Foundation